A STUDY OF TEACHING DURING THE INDUSTRIAL ERA 4.0: ENGLISH TEACHING OBSTACLES TO THE USE OF ICT IN EFL CLASSROOM CONTEXT - Isnani, Khoirunnisa; Fajarwati, Neni Desi (UNISAN JURNAL, 2024)
Technological developments in the Industrial Revolution era 4.0 provide benefits in various aspects including education. Likewise, the advancements in information and communication technology (ICT) have greatly enhanced the innovation of English language teaching and learning, providing new opportunities and methods for teachers to engage students with the language. However, technology also brings some significant challenges that need to be addressed. Therefore, this article investigates the significant challenges teachers face in integrating ICT into their classrooms and highlights the innovative strategies they implement to successfully navigate these obstacles. This qualitative descriptive study involved five English teachers as the research subjects to obtain data using structured interviews. Researchers found that The rapid advancements in technology impacted various aspects, including education aspect. The efficacy of English language acquisition is demonstrably enhanced by advancements in technology. However, the teachers faced some obstacles in integrating ICT into English teaching and learning, including technical constraints, incomplete ICT infrastructure in schools, and teachers’ lack expertise in utilizing ICTs in the learning process. In addressing these challenges, teachers have devised various strategies, including comprehensive preparation and inspection of all ICT equipment to be utilized in the learning process, using the personal internet network during the trouble network in the school, and requesting assistance from others who possess greater ICT skills. Consequently, the utilization of ICT can be implemented as mentioned from teachers’ perception which the benefits of ICT have been used for English teaching and learning process in Indonesian classroom context.